An approach to derive strength parameters of residual soils from DMT results - Nuno Cruz (2014)
Residual soils show a specific mechanical behaviour classified as on-conventional when compared with sedimentary transported soils, since the presence of a cemented matrix plays an important role on their strength and stiffness. Moreover, suction is frequent in natural profiles, which in residual soils creates several problems on the interpretation of in-situ test results. These two factors, cementation and suction, are contributing simultaneously as structuring factors. Correlations to deduce strength parameters in Portuguese granitic residual soils by Marchetti Dilatometer were previously established under a data base obtained in careful triaxial testing programs executed on undisturbed samples. However, the reference results were affected by sampling disturbance and space variability, and therefore somehow deviated from in-situ conditions. To solve these problems, a large calibration box was constructed to work with artificially cemented soils where DMT blades could be pre-installed and pushed-in. Water level, suction and seismic velocities were monitored during the experiment and a triaxial program was established in parallel on the same artificially cemented mixtures. As a result specific correlations to derive the cohesion intercept value and the angle of shearing resistance in saturated and unsaturated conditions were developed and subsequently tested in a well characterized experimental site. Herein, the results of that experimental framework are presented and discussed.